The Effect of Using Chain Writing Method on Students’ Writing Skill of Recount Text at Grade XI of SMA Swasta Daerah Air Joman in 2022/2023 Academic Year - Sundari Sundari; Putri Lidiana Permata Sari (English Teaching and Linguistics Journal (ETLiJ), 2023)
The intended of this study was to gather empirical data regarding the impact of chain writing on students' recount text writing. This study used a quantitative methodology and a quasi-experimental research design. The sample of this research was at the eleven grade students of SMASDA Air Joman in 2022/2023 Academic Year. There were the experimental and the control group. Each group consisted of 30 students. The experimental group was taught with chain writing method while the control group was taught with teacher’s conventional method. A written test was used as the research instrument, and the students' writing on the pre- and post-tests was graded using a writing rubric. According to the calculations, the experimental group's post-test mean scores were 79.13, while the control group's were 74.37. When using an independent sample t-test to test statistical hypotheses, the results showed that, on a scale of 5% significance ( 0.05), t0 was 3.015 and ttable was 2.002, meaning that t0 was greater than ttable. The instrument used in this research was a written test and the scoring of writing rubric was used to score the students’ writing on the pre test and post test. Based on the calculation, the post-test mean scores of the experimental group was 79.13 while that of the control group was 74.37. Then, the result of statistical hypothesis testing by using independent sample t-test found that on degree of significance 5% (α = 0.05), was 3.015 while was 2.002 or . As a result, Ho was rejected while Ha was accepted. In addition, the Cohen's formulation was used to determine the effect size of the chain writing method, and the result was 0.77. It was discovered that the chain writing method had a moderate effect, and it was possible to conclude that the chain writing method had a significant effect on students' writing skill of recount text at grade eleven of SMASDA air joman in the 2022/2023 academic year.